Bacteriological quality and safety of bottle food and associated factors among bottle-fed babies attending pediatric outpatient clinics of Government Health Institutions in Arba Minch, southern Ethiopia - Alebachew Marege; Belayneh Regassa; Mohammed Seid; Dagimawie Tadesse; Munira Siraj; Aseer Manilal (BMC, 2023)
Abstract Background Microbial contamination of baby bottle food has been identified as a significant public health concern, especially in developing countries, but it remains overlooked. Therefore, this study aimed to determine microbiological hazards, compliance with hygiene practices, and critical control points of contamination in baby bottle food in Arba Minch, southern Ethiopia. Objective To evaluate the bacteriological quality and prevalence of foodborne pathogens in baby bottle food and to identify associated factors among bottle-fed babies attending three government health institutions in Arba Minch, southern Ethiopia. Methods A cross-sectional study was conducted between February 24 and March 30, 2022. A total of 220 food samples, comprising four types prepared with different sources of materials, were collected from systematically selected bottle-fed babies attending health facilities. The data on sociodemographic characteristics, food hygiene, and handling practices were solicited by face-to-face interview using a semi-structured questionnaire. Food samples (10 mL) were quantitatively analyzed for total viable counts (TVC) and total coliform count (TCC) and qualitatively for the presence of common foodborne bacterial pathogens. Data were analyzed using SPSS; ANOVA and multiple linear regression analyses were done to identify factors influencing microbial counts. Results Results revealed that the means and standard deviations of TVC and TCC were 5.3 ± 2.3 log10 colony forming units (CFU)/mL and 4.1 ± 2.6 log10 CFU/mL, respectively. Of the various food samples analyzed, 57.3 and 60.5% had a TVC and TCC above the maximum acceptable limits, respectively. The result of the ANOVA showed that there was a significant difference in the mean score of TCV and TCC among the four types of food samples (p < 0.001). Enterobacteriaceae were found in the majority of positive food samples (79.13%), followed by Gram-positive cocci (20.8%). Salmonella spp., diarrheagenic Escherichia coli, and Staphylococcus aureus were the common foodborne pathogens detected in 8.6% of tested foods. The regression result revealed that the type of baby food, hand washing practices of mothers or caregivers, and sterilizing and disinfecting procedures of feeding bottles are independent determinants of bacterial contamination (p < 0.001). Conclusion The high microbial load and the presence of potential foodborne bacterial pathogens in the bottle food samples analyzed indicate unsanitary practices and the potential risk of exposure to foodborne pathogens in bottle-fed babies. Thus, interventions such as educating parents about proper hygiene practices, sterilizing feeding bottles and limiting bottle feeding practices are critical to reducing the risk of foodborne to bottle-fed infants.